Modelling the decrement in running intensity within professional soccer players - Delaney, J. A.; Thornton, H. R.; Rowell, A. E.; Dascombe, B. J.; Aughey, R. J.; Duthie, G. M. (Science and Medicine in Football, 2018)
Knowledge of the most intense periods of competitive soccer may assist in the development of specific training methodologies. Objectives: To quantify the peak running intensity of professional soccer and to establish the rate of decline in this intensity as a function of time. Methods: Activity profiles were obtained from 24 players across 40 professional matches. Peak values were calculated for moving averages 1-10 minutes in duration for relative distance (m/min), high-speed relative distance (HS m/min), average acceleration/deceleration (m·s2) and metabolic power (Pmet). To quantify the decrease in running intensity for longer moving average durations, each measure was evaluated relative to the moving average duration, as a power law relationship. Results: Peak relative distance and Pmet were lowest for central defenders (effect size [ES] = 0.79-1.84), whilst acceleration/deceleration intensity was highest for wide defenders (ES = 0.67-1.42). Differences in the rate of decline in running intensity between positions were considered trivial to small, indicating a similar rate of decline in running intensity across positions. Conclusions: Using power law, the peak running intensities of professional soccer can now be predicted as a function of time, providing coaches with a useful tool for the prescription and monitoring of specific training drills.